Ultrafast Laser Pulses Enable One-Step Graphene Patterning on Woods and Leaves for Green Electronics - Le, Truong-Son Dinh; Park, Sangbaek; An, Jianing; Lee, Pooi See; Kim, Young-Jin (WILEY-V C H VERLAG GMBH, 2019)
Fast, simple, cost-efficient, eco-friendly, and design-flexible patterning of high-quality graphene from abundant natural resources is of immense interest for the mass production of next-generation graphene-based green electronics. Most electronic components have been manufactured by repetitive photolithography processes involving a large number of masks, photoresists, and toxic etchants; resulting in slow, complex, expensive, less-flexible, and often corrosive electronics manufacturing processes to date. Here, a one-step formation and patterning of highly conductive graphene on natural woods and leaves by programmable irradiation of ultrafast high-photon-energy laser pulses in ambient air is presented. Direct photoconversion of woods and leaves into graphene is realized at a low temperature by intense ultrafast light pulses with controlled fluences. Green graphene electronic components of electrical interconnects, flexible temperature sensors, and energy-storing pseudocapacitors are fabricated from woods and leaves. This direct graphene synthesis is a breakthrough toward biocompatible, biodegradable, and eco-friendlily manufactured green electronics for the sustainable earth.
Keywords: AMORPHOUS-CARBON; FEMTOSECOND; DIAMOND; GRAPHITIZATION; POLYIMIDE; SUPERCAPACITORS; TRANSFORMATION; PYROLYSIS; PRESSURE; ABLATION